Psychometric Properties of a Questionnaire to Assess Perceptions of Corporal Expression in Future Spanish Teachers - Rojo-Ramos, Jorge (2022)
Corporal expression is a content that is forgotten by most educators but has been proved to bring numerous benefits to students of all ages. Teacher perceptions and beliefs play a fundamental role in the teaching-learning process, influencing students to a great extent. This study aims to present the factor structure and reliability of a questionnaire for the assessment of teachers’ perceptions about corporal expression. The sample consisted of 212 Spanish prospective teachers who completed the questionnaire to assess their readiness and appreciation about corporal expression. Exploratory and confirmatory factor analyses, as well as reliability testing, were carried out. The results showed a factor structure with 3 dimensions (pleasure, preference, and evaluation of corporal expression) composed of 23 items with good and excellent goodness-of-fit values and high reliability (Cronbach’s alpha = 0.71–0.93). Thus, the questionnaire can be considered a quick and easy-to-apply tool to analyze prospective teacher’s perceptions about their preparation to address their students’ corporal expression, allowing stakeholders to take actions to promote it.